Strong-adsorption super-wetting self-assembly micromolecule as well as preparation method and application thereof
By using a bito-tooth anchored ultrawet carbazolyl aromatic self-assembled small molecule material as the hole transport layer, the problems of uneven adsorption and weak adhesion of self-assembled small molecules on the ITO substrate are solved, and the performance and stability of perovskite solar cells are significantly improved.
Patent Information
- Application Number
- CN202411668951.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, self-assembled small molecule hole transport materials have uneven adsorption and weak adhesion on the ITO substrate, resulting in insufficient carrier extraction and energy loss, which seriously reduces the performance and stability of perovskite solar cells.
A bitoto-anchored ultrawetting carbazolyl aromatic self-assembled small molecule material is used, which enhances its adsorption capacity on the ITO substrate and the superwetting ability of the perovskite layer by introducing biarrosine conjugated groups and phosphate groups at the 3,6 positions of the carbazole.
The photoelectric conversion efficiency and stability of perovskite solar cells are improved. The photoelectric conversion efficiency of a single perovskite solar cell reaches 22.83%, and the efficiency of perovskite/crystalline silicon stacked solar cell is close to 30%, while enhancing the moisture and heat stability of the device.
Smart Images

Figure CN119504855A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a strongly adsorbed super-wetting self-assembled small molecule hole transport material, a preparation method and a perovskite solar cell using the self-assembled small molecule as a hole transport layer. Background Art
[0002] The development and use of clean energy is one of the important breakthrough directions for solving the energy crisis and achieving the goals of "carbon peak and carbon neutrality". As an auxiliary and supplementary energy source, solar photovoltaic technology has ushered in rapid development, and the cost of power generation is also declining rapidly. With the advancement of photovoltaic technology, solar energy, as a clean and renewable energy source, will surely become one of the important energy sources for sustainable development. As a representative of the third-generation photovoltaic technology, perovskite solar cells have unique flexible compatibility and large-area preparation potential, bringing unprecedented opportunities to photovoltaics, the Internet of Things, new energy vehicles and even aerospace. Its photoelectric conversion efficiency (PCE) has achieved great success from 3.8% to 26.7% in just over ten years.
[0003] Compared with conventional (nip) PSCs, inverted (pin) devices have several advantages, including low-temperature processing, high stability, low hysteresis effect, and integration with commercial c-Si technology. Typically, pin devices consist of a conductive glass substrate, a hole transport layer, a perovskite layer, an electron transport layer, and a metal electrode. Among them, the hole transport layer plays a role in adjusting the interface energy level, regulating the nucleation of perovskite and charge extraction and transport, and has an important influence on the device efficiency and stability. In recent years, self-assembled small molecule (SAM) hole transport materials with anchoring groups (phosphoric acid, carboxylic acid, boric acid, sulfonic acid, thiol, and silane, etc.), linking groups (alkyl, phenyl), and functional groups (carbazole, triphenylamine, phenothiazine, thiophene, acridine, etc.) have attracted much attention and have been widely used in single-junction pin perovskite cells and stacked devices. They are orderly anchored on the surface of indium tin oxide (ITO) substrates through dehydration condensation between the anchoring groups and the hydroxyl groups on the surface of the ITO substrate. The functional groups regulate the substrate work function and interface properties, and the linking groups regulate the charge extraction and transport properties. Due to its electron-rich properties and excellent hole injection ability, carbazole is currently the most widely used functional group in SAM, but the hydrophobicity of polycyclic carbazole increases the complexity of preparing high-quality perovskite films. For example, the invention patent with publication number CN118239979A provides a self-assembled monolayer material and its preparation method and application. In the structure of its self-assembled monolayer material, the phosphate group is anchored on the substrate of the battery as an anchoring group, which improves the coverage of the molecule on the substrate, is conducive to passivating interface defects, and the phosphate group and the substrate of the battery have a strong force, which can enhance the interface stability. At the same time, a series of aromatic conjugated groups are introduced with triphenylamine as the main body, which can regulate the interface energy level to make it more compatible with the valence band of the perovskite, thereby facilitating the improvement of the molecule's extraction performance for holes. In addition, the R group in the self-assembled monolayer material can also effectively increase the force between the material and the perovskite, thereby improving the wettability between the hole transport layer and the perovskite, further improving the hole transport effect, and thus facilitating the improvement of the photoelectric conversion efficiency of the device. For another example, the invention patent with publication number CN116193942 provides the preparation of perovskite solar cells based on one-step spin coating of self-assembled small molecules, in which the self-assembled small molecules are directly added to the perovskite precursor solution to prepare the hole transport layer and the perovskite layer in one step. The self-assembled small molecules are self-assembled small molecules containing anchoring groups, and the anchoring groups include at least one of acetate groups, boric acid groups, thiol groups and phosphonic acid groups.
[0004] Although the use of Mx-SAM or Co-SAM can slightly improve the manufacturing yield of carbazole-based substrates, the intrinsic superwetting hole transport layer without any treatment is more popular on the production line. In addition, the anchoring of SAM usually suffers from uneven coverage and weak adhesion, which ultimately leads to insufficient carrier extraction and energy loss, seriously reducing the performance and stability of the device. Therefore, it is imperative to develop a new type of superwetting light-irradiated self-assembled small molecule hole transport material that can be strongly adsorbed on ITO substrates to improve the performance and stability of the device. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a preparation method and application of a super-wettable carbazole-based aromatic self-assembled small molecule hole transport material using bidentate anchoring. The material itself has stronger adsorption energy on ITO and provides a super-wettable hole transport bottom layer for perovskite. When used in perovskite solar cells, the performance and stability of perovskite solar cells can be simultaneously improved.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a strongly adsorbed superwetting self-assembling small molecule having a structure shown in Formula I:
[0008]
[0009] In Formula I, is an aromatic conjugated group, R 1 is hydrogen, methyl, methoxy or halogen, R 2 It is a phosphonic acid group, a carboxylic acid group, or a cyanophosphoric acid group.
[0010] Preferably, Any one of the following groups:
[0011]
[0012] The dotted line indicates the connection position of the group
[0013] In a second aspect, the present invention provides a method for preparing a sulfur-containing nitrogen heteropolycyclic self-assembly small molecule, comprising the following steps:
[0014] (1): The compound represented by the 3,6-dibromocarbazole derivative formula A is used as a starting material to undergo a borate esterification reaction with biboric acid pinacol ester B to obtain a compound represented by the formula C. The reaction formula is as follows:
[0015]
[0016] (2): The compound represented by formula C undergoes a Suzuki coupling reaction with the compound represented by formula D to generate the compound represented by formula E. The reaction formula is as follows:
[0017]
[0018] (3): The compound represented by Formula E undergoes a nucleophilic substitution reaction with Formula F to generate a compound represented by Formula G. The reaction formula is as follows:
[0019]
[0020] (4): The compound represented by formula G is hydrolyzed with trimethylsilyl bromide to obtain the compound represented by formula I, and the reaction formula is as follows:
[0021]
[0022] Among them, R 1 is hydrogen, methyl, methoxy or halogen, R 2 is phosphonic acid, carboxylic acid, cyanophosphate, R 3 is a phosphonate group, a carboxylate group, a cyanophosphate group, Any one of the following groups:
[0023]
[0024] Preferably, the catalyst for the borate esterification reaction in step (1) is a palladium catalyst; more preferably, the palladium catalyst is Pd(dppf)Cl2.
[0025] Preferably, in step (1), the molar mass ratio of the compound of formula A to the compound of formula B is 1:(2.0-4.0); for example, it can be 1:2.0, 1:2.4, 1:2.8, 1:3.2, 1:3.6, 1:4.0.
[0026] Preferably, the solvent for the borate esterification reaction in step (1) comprises any one of toluene, N,N-dimethylformamide or N,N-dimethylacetamide, and more preferably, the solvent is toluene.
[0027] Preferably, the temperature of the borate esterification reaction in step (1) is 80-120°C, for example, 80°C, 90°C, 100°C, 110°C, or 120°C.
[0028] Preferably, the borate esterification reaction time in step (1) is 16-24 h, for example, it can be 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h.
[0029] The catalyst for the Suzuki coupling reaction in step (2) is a palladium catalyst. More preferably, the palladium catalyst is Pd(PPh3)4.
[0030] Preferably, in step (2), the molar mass ratio of the compound C to the compound D is 1:(4.0-6.0), for example, 1:4.0, 1:4.4, 1:4.8, 1:5.2, 1:5.6, 1:6.0;
[0031] Preferably, the solvent for the Suzuki coupling reaction in step (2) comprises any one of dichloromethane, tetrahydrofuran, toluene and 1,4-dioxane; more preferably, the solvent is tetrahydrofuran;
[0032] Preferably, the temperature of the nucleophilic substitution reaction in step (2) is 60-110°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C;
[0033] Preferably, the time of the nucleophilic substitution reaction in step (2) is 8-12 h, for example, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h;
[0034] The catalyst for the nucleophilic substitution reaction in step (3) is a palladium catalyst. More preferably, the palladium catalyst is palladium acetate.
[0035] Preferably, in step (3), the molar mass ratio of the compound C to the compound D is 1:(4.0-8.0), for example, 1:4.0, 1:4.5, 1:5.0, 1:5.5, 1:6.0, 1:6.5, 1:7.0, 1:7.5, 1:8.0;
[0036] Preferably, the solvent for the nucleophilic substitution reaction in step (3) comprises any one of dichloromethane, tetrahydrofuran, toluene and 1,4-dioxane; more preferably, the solvent is 1,4-dioxane;
[0037] Preferably, the temperature of the nucleophilic substitution reaction in step (3) is 60-110°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C;
[0038] Preferably, the time of the nucleophilic substitution reaction in step (3) is 12-36 h, for example, it can be 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, 26 h, 28 h, 30 h, 32 h, 34 h, 36 h;
[0039] Preferably, in step (4), the molar mass ratio of the compound of formula E to trimethylsilyl bromide is 1:(40.0-60.0), for example, 1:40.0, 1:45.0, 1:50.0, 1:55.0, 1:60.0;
[0040] Preferably, the solvent for the hydrolysis reaction in step (4) comprises any one of dichloromethane, tetrahydrofuran or 1,4-dioxane, and more preferably, the solvent is dichloromethane;
[0041] Preferably, the temperature of the hydrolysis reaction in step (4) is 25-40°C, for example, 25°C, 30°C, 35°C, 40°C;
[0042] Preferably, the hydrolysis reaction time in step (4) is 12-24 h, for example, it can be 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h.
[0043] In a third aspect, the present invention provides an application of a strongly adsorbed superwetting self-assembled small molecule as a hole transport layer in a perovskite solar cell. That is, the present invention provides a hole transport layer, wherein the hole transport layer uses the above-mentioned strongly adsorbed superwetting self-assembled small molecule as a hole transport material.
[0044] In a fourth aspect, the present invention provides a perovskite solar cell, wherein the perovskite solar cell uses the above-mentioned strongly adsorbed superwetting self-assembled small molecules as a hole transport layer. Specifically, the perovskite solar cell is a pin type, comprising an anode layer, a hole transport layer, a perovskite active layer, an electron transport layer and a cathode layer stacked in sequence.
[0045] Preferably, the anode layer is ITO conductive glass.
[0046] Preferably, the thickness of the anode layer is 180-200 nm, for example, 180 nm, 190 nm, or 200 nm.
[0047] Preferably, the thickness of the hole transport layer is 2-6 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, or 6 nm.
[0048] Preferably, the perovskite active layer material is ABX3; wherein A is CH3NH3 + 、HC(NH2)2 + , Cs + One or more of, B is Pb 2+ Sn 2+ One or more of, X is 1 - Br - , Cl - One or more of .
[0049] Preferably, the thickness of the perovskite active layer is 450-550 nm, for example, 450 nm, 460 nm, 480 nm, 500 nm, 520 nm, 540 nm, or 550 nm.
[0050] Preferably, the electron transport layer is a BCP-modified 60 electron transport layer.
[0051] Preferably, the thickness of the electron transport layer is 20-30 nm, for example, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, or 30 nm.
[0052] Preferably, the cathode layer is a silver electrode.
[0053] Preferably, the cathode layer has a thickness of 100-150 nm, for example, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, or 150 nm.
[0054] The present invention realizes a method for preparing a strongly adsorbed superwetting self-assembling small molecule and its application in perovskite solar cells through the above scheme. Compared with the prior art, the strongly adsorbed superwetting self-assembling small molecule material provided by the present invention adopts a bidentate anchoring connection anchoring group instead of the currently commonly used single anchoring group; the advantages of the material are: (1) compared with the traditional carbazole-type self-assembling small molecule, the present application does not rely on the NH group to couple the alkyl / aromatic phosphoric acid, but introduces two aromatic conjugated groups from the 3 and 6 positions of carbazole, and then connects phosphoric acid. This method is more unique and breaks the inertial thinking of the traditional carbazole self-assembling molecule design. (2) By connecting aromatic conjugated groups on both sides of carbazole, not only the charge transfer in the molecule is increased, the hole transport performance of the material is provided, and the stability against ultraviolet radiation is maintained, but also the anchoring group of the connected diaromatic phosphonic acid ensures the robust adsorption on the planar ITO and velvet silicon, showing excellent resistance to moisture and heat; (3) Compared with the traditional carbazole self-assembly molecules, the reverse carbazole diaromatic phosphonic acid strategy designed in this application retains the NH group, which can not only interact with perovskite and stabilize the perovskite solar cell, but also has super-wetting properties, which is very conducive to the formation of a uniform and dense film on the surface of the perovskite. The perovskite solar cell prepared by using the strongly adsorbed super-wetting self-assembly small molecule provided by the present invention as a hole transport layer has excellent performance and high stability, and the photoelectric conversion efficiency on the 1.68eV wide band gap perovskite reaches 22.83%, and the photoelectric conversion efficiency of nearly 30% is also achieved in the application of perovskite / crystalline silicon stacked solar cells. In addition, the preparation method of the strongly adsorbed super-wetting self-assembly small molecule provided by the present invention is simple, mild, easy to control, high in yield, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] The present invention may be better understood by referring to the following description given in conjunction with the accompanying drawings, wherein the same or similar reference numerals are used throughout the drawings to represent the same or similar components. The accompanying drawings, together with the following detailed description, are included in and form a part of this specification and are used to further illustrate the preferred embodiments of the present invention and to explain the principles and advantages of the present invention. In the drawings:
[0056] Figure 1 The contact angle test and optical photograph of the deposited perovskite film provided in Example 2 of the present invention;
[0057] Figure 2 This is a diagram showing the mechanism of action of Example 2 and Comparative Example 1 of the present invention with perovskite;
[0058] Figure 3 This is an infrared spectrum of an atomic force microscope after self-assembled small molecules are deposited on a planar ITO surface in Example 3 of the present invention;
[0059] Figure 4 A schematic diagram of the device structure of a single-cell perovskite solar cell provided in Example 4 of the present invention;
[0060] Figure 5 A schematic diagram of the device structure of a perovskite / crystalline silicon tandem solar cell provided in Example 4 of the present invention;
[0061] Figure 6 The current density and voltage (JV) curves of the single nodes prepared in Comparative Example 1 and Example 6;
[0062] Figure 7 The current density and voltage (JV) curves of the perovskite / crystalline silicon tandem solar cells prepared in Comparative Example 2 and Example 7;
[0063] Figure 8 The light stability test diagram of the single-cell perovskite solar cell prepared in Comparative Example 1 and Example 6 under MPP;
[0064] Fig. 9 Performance comparison of bidentate-anchored superwettable aromatic self-assembled monolayers used as hole-selective layers in inverted wide-bandgap perovskite solar cells. DETAILED DESCRIPTION
[0065] Embodiments of the present invention will be described below with reference to the accompanying drawings. Elements and features described in one drawing or one embodiment of the present invention may be combined with elements and features shown in one or more other drawings or embodiments. It should be noted that for the purpose of clarity, the representation and description of components and processes that are not related to the present invention and are known to those of ordinary skill in the art are omitted in the drawings and descriptions.
[0066] The purpose of the present invention is to provide a preparation method and application of a super-wettable self-assembled small molecule hole transport material anchored with diaromatic phosphonic acid and strongly adsorbed, and the super-wettable self-assembled small molecule provided by the present invention is used as a hole transport material for both PIN-type perovskite solar cells and stacked solar cells, and the device has excellent performance and high stability.
[0067] Example 1
[0068] Specifically, the strongly adsorbed superwetting self-assembling small molecule of Example 1 of the present invention has a structure shown in Formula I-1:
[0069]
[0070] Synthesis route of strongly adsorbed superwetting self-assembly small molecule I-1:
[0071]
[0072] (1) Synthesis of intermediate compound 1
[0073] Under nitrogen atmosphere, 3,6-dibromocarbazole (2.45 g; 7.5 mmol), diboronic acid pinacol ester (7.62 g; 30 mmol), Pd(dppf)Cl2 (0.15 g; 0.21 mmol) and potassium acetate (2.90 g; 30 mmol) were dissolved in anhydrous toluene (40 mL). The reaction mixture was refluxed at 120 ° C for 20 hours. After cooling to room temperature, the solvent was removed under reduced pressure. The residue was dissolved in dichloromethane. The mixture was filtered through a celite pad, and the filtrate was washed with saturated brine (3×30 mL) and then dried over anhydrous magnesium sulfate. After evaporating the solvent under reduced pressure, the crude product was purified by silica gel column chromatography (petroleum ether: ethyl acetate = 10:1 as eluent) to obtain intermediate compound 1 with a yield of 79%.
[0074] 1 H NMR (500MHz, Chloroform-d) δ8.65 (s, 2H), 8.20 (s, 1H), 7.86 (dd, J = 8.1, 1.0Hz, 2H), 7.48–7.36 (m, 2H), 1.39 (s, 24H).
[0075] (2) Synthesis of intermediate compound 2
[0076] Under nitrogen protection, intermediate compound 1 (340 mg; 0.8 mmol), 4-bromoiodobenzene (1.15 g; 4.1 mmol) and Pd(PPh3)4 (37 mg; 0.032 mmol) were dissolved in a mixture of 10 mL tetrahydrofuran (THF) and 2 mL 2 molar sodium carbonate aqueous solution, and the reaction mixture was heated to reflux for 8 hours. After cooling to room temperature, the resulting mixture was washed with saturated brine and extracted with ethyl acetate. The organic layer was dried over anhydrous magnesium sulfate, and the solvent was removed under reduced pressure. The crude product was purified by silica gel column chromatography (petroleum ether: dichloromethane = 5:1 as eluent) to obtain intermediate compound 2 with a yield of 67%.
[0077] 1 H NMR(500MHz,Chloroform-d)δ8.29(d,J=1.6Hz,2H),8.17(s,1H),7.66(d,J=1.8 Hz,1H),7.64(d,J=1.8Hz,1H),7.59(d,J=1.7Hz,8H),7.52(s,1H),7.50(s,1H).
[0078] (3) Synthesis of intermediate compound 3
[0079] Under nitrogen protection, intermediate compound 2 (400 mg, 0.84 mmol), diethyl phosphite (0.9 mL, 6.72 mmol), Pd(OAc)2 (19 mg, 0.084 mmol), dppf (93 mg, 0.17 mmol) and potassium acetate (82 mg, 0.84 mmol) were dissolved in 10 mL 1,4-dioxane, and the mixture was heated to reflux for 16 hours. After cooling to room temperature, the solvent was removed under reduced pressure, and the residue was dissolved in dichloromethane. The solution was washed with saturated brine, and the organic layer was dried over anhydrous MgSO4. After evaporating the solvent under reduced pressure, the crude product was purified by silica gel column chromatography (dichloromethane: methanol = 20: 1 as eluent), and the intermediate compound 3 was obtained by recrystallization (acetone: petroleum ether = 1: 50) with a yield of 84%.
[0080] 1 H NMR(500MHz,Chloroform-d)δ8.69(s,1H),8.51–8.33(m,2H),7.94(dd,J=12.9,8.2Hz,4H),7.84(dd,J=8.2 ,3.9Hz,4H),7.74(dd,J=8.4,1.6Hz,2H),7.57(d,J=8.4Hz,2H),4.31–4.06(m,8H),1.39(t,J=7.1Hz,12H). 31 P NMR(202MHz,Chloroform-d)δ19.45.
[0081] (4) Synthesis of Strongly Adsorbed Superwetting Self-Assembly Small Molecule I-1
[0082] The intermediate compound 3 (100 mg, 0.169 mmol) was dissolved in 20 mL of dichloromethane, and trimethylsilyl bromide (1.0 mL, 8.83 mmol) was slowly added dropwise. The mixture was stirred at room temperature for 12 h, quenched with 10 mL of saturated sodium chloride solution, and then 20 mL of dichloromethane was added and stirred for 2 h to obtain a white milky mixture. After filtering, the solid was washed with water and ether to obtain a strongly adsorbed superwetting self-assembling small molecule I-1 with a yield of 82%.
[0083] 1 H NMR (500MHz, DMSO-d6) δ11.52(s,1H),8.69(s,2H),7.91(d,J=4.6Hz,4H),7.84–7.76(m,6H),7.61(d,J=8.5Hz,2H).
[0084] 13 C NMR (126MHz, DMSO-d6) δ143.94,143.91,140.61,132.86,131.69,131.61,131.40,130.62,126.63,126.51,125.40,123.83,119.43,112.09.
[0085] 31 P NMR (202 MHz, DMSO-d6) δ 13.07.
[0086] HRMS m / z calcd.for C 24 H 19 NO6P2:479.0688.Found:480.0759[M+H].
[0087] Anal.calcd.for C 24 H 19 NO6P2:C 60.13,H 4.00,N 2.92,O 20.03.Found:C 60.29,H 3.86,N 2.87,O 19.70.
[0088] In Example 1 of the present invention, in the process of preparing intermediate compound 1, considering the incomplete reaction and the generation of by-products (3-bromo-6-(4,4,5,5-tetramethyl-1,3,2-dioxabor-2-yl)-9H-carbazole), this embodiment uses a 4-fold dose of biboronic acid pinacol ester for reaction, but the excess raw materials and by-products will affect the purification, and intermediate 1 carries a borate ester group and has a strong adsorption on the silica gel column. In this embodiment 1, the best eluent (petroleum ether: ethyl acetate = 10: 1) is screened from a variety of solvents. In the process of preparing intermediate 3, since the diethyl phosphite raw material used is 8 times the equivalent of intermediate 2, a small amount of by-products with similar polarity will be carried during the purification process. After trying various methods, it was found that recrystallization with acetone: petroleum ether = 1: 50 as a solvent can be further purified without affecting the subsequent hydrolysis reaction. In general, the preparation method provided in Example 1 of the present invention is simple in process, mild in conditions, easy to control, high in yield, and has broad application prospects.
[0089] Example 2
[0090] In this Example 2, water contact angle tests were performed on Formula I-1 and the first aromatic self-assembled small molecule MeO-PhPACz, and optical photographs of the deposited perovskite films were taken ( Figure 1 ), the results show that the water contact angle of formula I-1 is significantly reduced, and as a super-wetting hole transport layer of the perovskite bottom layer, the deposited perovskite film has excellent quality. This shows that the I-1 molecule exhibits excellent wettability to the perovskite precursor solution and can improve the quality of the perovskite film.
[0091] Figure 2 Schematic diagram of the mechanism of action of this embodiment and perovskite.
[0092] Example 3
[0093] In this Example 3, the thin films of Formula I-1 and the first aromatic self-assembled small molecule MeO-PhPACz deposited on ITO were tested by atomic force microscope infrared spectroscopy ( Figure 3 ). In order to verify the stable adsorption of Formula I-1 on ITO, the ITO / SAM surface was rinsed with DMF to remove any unadsorbed or physically adsorbed components. The infrared spectroscopy test results based on atomic force microscopy showed that the infrared response of the ITO / I-1 sample was higher, indicating that the bisaromatic phosphonic acid provided greater adsorption energy and had excellent chemical stability.
[0094] Example 4
[0095] This embodiment 4 provides a pin-type perovskite solar cell, the cell structure is as follows Figure 4As shown, it includes an anode layer, a hole transport layer, a perovskite active layer, an electron transport layer and a cathode layer in sequence, and the hole transport layer is prepared from the strongly adsorbed super-wetting self-assembled small molecule hole transport material described in the above technical solution.
[0096] This embodiment has no special requirements on the composition of the material of the anode layer, and any material known to those skilled in the art for the anode layer of a solar cell can be used, such as transparent conductive metal oxide ITO or fluorine-doped tin oxide (FTO).
[0097] In this embodiment, the electron transport layer is a BCP-modified 60 electron transport layer.
[0098] In this embodiment, the perovskite light absorbing layer material is ABX3; wherein A is CH3NH3 + 、HC(NH2)2 + , Cs + One or more of, B is Pb 2+ Sn 2+ One or more of, X is 1 - Br - , Cl - One or more of .
[0099] In this embodiment, the material of the hole transport layer adopts the strongly adsorbed super-wetting self-assembled small molecule hole transport material described in the above technical solution, and the thickness of the hole transport layer is preferably 2-6 nm, and more preferably 3-5 nm.
[0100] In this embodiment, the material of the cathode layer is preferably silver or gold, and the thickness of the cathode layer is preferably 100 nm-150 nm, more preferably 110 nm-130 nm.
[0101] In this embodiment, in the perovskite solar cell, a metal wire is deposited at one end of the transparent conductive metal oxide anode layer, the metal wire is connected to the other end of the load or the test device, and the anode layer is connected to the other end of the load or the test device. The incident light is incident from the direction of the substrate. The main function of the hole transport layer is to transport holes and block electrons; the main function of the active layer is to absorb photons and convert them into excitons, so that the excitons are separated into electrons and holes at the donor-acceptor interface; the function of the electron transport layer is to transport electrons and block holes; the function of the metal electrode is to collect carriers.
[0102] Example 5
[0103] This embodiment 5 provides a perovskite / crystalline silicon perovskite solar cell, the cell structure is as follows Figure 5As shown, it includes a silicon bottom battery, a composite layer, a hole transport layer, a perovskite active layer, an electron transport layer, a buffer layer, a semi-transparent cathode layer and an anti-reflection layer in sequence, and the hole transport layer is prepared from the strongly adsorbed super-wetting self-assembled small molecule hole transport material described in the above technical solution.
[0104] In this embodiment, the silicon bottom cell is an n-type Cz silicon heterojunction solar cell without metal grid lines.
[0105] In this embodiment, the composite layer is a transparent conductive metal oxide ITO, and the thickness of the composite layer is preferably 3nm-25nm, and more preferably 5nm-10nm.
[0106] In this embodiment, the electron transport layer is a BCP-modified 60 electron transport layer.
[0107] In this embodiment, the perovskite light absorbing layer material is ABX3; wherein A is CH3NH3 + 、HC(NH2)2 + , Cs + One or more of, B is Pb 2+ Sn 2+ One or more of, X is 1 - Br - , Cl - One or more of .
[0108] In this embodiment, the material of the hole transport layer adopts the strongly adsorbed super-wetting self-assembled small molecule hole transport material described in the above technical solution, and the thickness of the hole transport layer is preferably 2-6 nm, and more preferably 3-5 nm.
[0109] In this embodiment, the buffer layer is tin oxide deposited by atomic layer deposition, and the thickness of the buffer layer is preferably 10-20 nm, and more preferably 12-15 nm.
[0110] In this embodiment, the semi-transparent cathode layer is indium zinc oxide (IZO, In2O3 / ZnO=90 / 10) prepared by magnetron sputtering, and the thickness of the semi-transparent cathode layer is preferably 50-200 nm, and more preferably 90-110 nm.
[0111] In this embodiment, the anti-reflection layer is magnesium fluoride deposited by thermal evaporation, and the thickness of the anti-reflection layer is preferably 100-200 nm, and more preferably 130-160 nm.
[0112] In the perovskite solar cell described in this embodiment, a metal wire is deposited on one end of the p-type side of the silicon heterojunction bottom cell, the metal wire is connected to the other end of the load or the test device, the semi-transparent cathode layer is connected to the other end of the load or the test device, and the incident light is incident from the direction of the perovskite top cell. The main function of the hole transport layer is to transport holes and block electrons; the main function of the active layer is to absorb photons and convert them into excitons, so that the excitons are separated into electrons and holes at the donor-acceptor interface; the function of the electron transport layer is to transport electrons and block holes; the function of the composite layer is to maintain the charge neutrality of the photogenerated charge carriers in the sub-cell, and the function of the metal electrode is to collect carriers.
[0113] Example 6
[0114] This embodiment provides a method for preparing a pin-type perovskite solar cell of embodiment 4, which comprises the following steps:
[0115] 1. ITO glass substrate cleaning. The substrate cleaning sequence is to use ultrasonic cleaning in detergent, deionized water and ethanol for 20 minutes. Then the ITO substrate is dried in a 70°C oven for 1 hour and then treated with ultraviolet ozone (UVO) for 30 minutes.
[0116] 2. Prepare a hole transport layer on the ITO conductive layer. Add an ethanol solution of the molecule of formula I-1 (2 mg mL -1 ) was spin-coated on the ITO conductive layer at a speed of 3000 rpm, and then annealed at 100° C. for 10 minutes to prepare a hole transport layer.
[0117] 3. Prepare the perovskite active layer. Configure the wide-bandgap perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 precursor solution (1.68eV), FAI, MABr, CsI, PbBr2, MAI, PbI2 were added to 1mL DMF / DMSO (v / v, 4:1) solution. Then 100μL of the perovskite precursor solution was directly spin-coated onto the hole transport layer, first at 1500r / min for 10s, then at 3500r / min for 35s. The resulting film was then transferred to a hot stage and annealed at 100°C for 30 minutes to obtain a perovskite film.
[0118] 4. Deposit an electron transport layer on the perovskite layer. Use thermal evaporation to prepare 25nm thick C60 and 8nm thick BCP on the prepared perovskite film.
[0119] 5. Finally, a 120 nm thick Ag electrode was prepared by thermal evaporation to obtain a pin-type perovskite solar cell.
[0120] Comparative Example 1
[0121] 1. ITO glass substrate cleaning. The substrate cleaning sequence is to use ultrasonic cleaning in detergent, deionized water, acetone and ethanol for 20 minutes. Then the ITO substrate is dried in a 70°C oven for 1 hour and then treated with ultraviolet ozone (UVO) for 20 minutes.
[0122] 2. Prepare a hole transport layer on the ITO conductive layer. The ethanol solution of the first aromatic self-assembled small molecule MeO-PhPACz (2 mg mL -1 ) was spin-coated on the ITO conductive layer at a speed of 3000 rpm, and then annealed at 100° C. for 30 minutes to prepare a hole transport layer.
[0123] 3. Prepare the perovskite active layer. Configure the wide-bandgap perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 precursor solution (1.68eV), FAI, MABr, CsI,
[0124] PbBr2, MAI, and PbI2 were added to 1 mL of DMF / DMSO (v / v, 4:1) solution. Then 100 μL of the perovskite precursor solution was directly spin-coated onto the hole transport layer, first at 1500 r / min for 10 s, then at 3500 r / min for 35 s. The resulting film was then transferred to a hot stage and annealed at 100 °C for 30 minutes to obtain a perovskite film.
[0125] 4. Deposit an electron transport layer on the perovskite layer. Use thermal evaporation to prepare 25nm thick C60 and 8nm thick BCP on the prepared perovskite film.
[0126] 5. Finally, a 120 nm thick Ag electrode was prepared by thermal evaporation to obtain a pin-type perovskite solar cell.
[0127] Example 7
[0128] This embodiment provides a method for preparing a perovskite / crystalline silicon perovskite solar cell according to embodiment 5, which comprises the following steps:
[0129] 1. Preparation of silicon heterojunction bottom cells. M6Czochralski n-Si wafers with a resistivity of 1.2-1.5Ω and a thickness of 130μm were used to manufacture Si bottom cells. A double-sided random pyramid texture was obtained using a KOH aqueous solution, and the pyramid height distribution on both sides was about 1.5-2.5μm. The wafer was cleaned with a standard RCA process and immersed in a dilute hydrofluoric acid solution, and then transferred to a deposition device (AKT-25KAXi PECVD system). Radio frequency plasma enhanced chemical vapor deposition was used to prepare a surface passivation stack, depositing about 6nm of hydrogenated intrinsic a-Si:H and 14nm of hydrogenated n-doped nc-Si:H on the front side. Subsequently, 8nm of hydrogenated intrinsic-Si:H and 10nm of hydrogenated p-doped a-Si:H layers were deposited on the back side. The opening area is 12×12mm 2 Using an alignment mask, ITO layers with a thickness of 10 nm and 115 nm were prepared on the front and back sides by DC sputtering, respectively. To recover the sputtering damage, a 10-min annealing step at 200 °C in ambient air was also performed. The wafer was then laser-etched into 25 × 25 mm 2 size.
[0130] 2. Silicon heterojunction bottom cell cleaning: The substrate was cleaned by ultrasonic cleaning in ethanol for 20 minutes, and then the ITO substrate was dried in a 70°C oven for 1 hour and then treated with ultraviolet ozone (UVO) for 10 minutes.
[0131] 3. Prepare a hole transport layer on a silicon heterojunction bottom cell. Add an ethanol solution of the molecule of formula I-1 (2 mg mL -1 ) was spin-coated on the ITO conductive layer at a speed of 3000 rpm, and then annealed at 100° C. for 10 minutes to prepare a hole transport layer.
[0132] 4. Prepare the perovskite active layer. Configure the wide-bandgap perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 precursor solution (1.68eV), FAI, MABr, CsI, PbBr2, MAI, PbI2 were added to 1mL DMF / DMSO (v / v, 4:1) solution. Then 100μL of the perovskite precursor solution was directly spin-coated onto the hole transport layer, first at 1500r / min for 10s, then at 3500r / min for 35s. The resulting film was then transferred to a hot stage and annealed at 100°C for 30 minutes to obtain a perovskite film.
[0133] 5. Deposit an electron transport layer on the perovskite layer. A 25 nm thick C60 layer was prepared on the prepared perovskite film by thermal evaporation.
[0134] 6. Deposit a buffer layer on the electron transport layer. Deposit 13nm tin oxide as a sputtered buffer layer by atomic layer deposition system. The processing sequence of ALD SnO2 deposition is: 0.15s TDMASn pulse, 12s purge (50sccm Ar), 0.33s deionized water pulse, 12s purge (50sccm Ar), for a total of 120 cycles.
[0135] 7. Magnetron sputtering of transparent electrode IZO on the buffer layer. At room temperature, 100 nm IZO (sheet resistance of 30-40 Ω / sq, radio frequency (RF) power of 45 W) was sputtered on the prepared buffer layer.
[0136] 8. Deposit an anti-reflection layer on the transparent electrode. 150nm of MgF2 is deposited on the prepared transparent electrode.
[0137] Comparative Example 2
[0138] 1. Preparation of silicon heterojunction bottom cells. M6Czochralski n-Si wafers with a resistivity of 1.2-1.5Ω and a thickness of 130μm were used to manufacture Si bottom cells. A double-sided random pyramid texture was obtained using a KOH aqueous solution, and the pyramid height distribution on both sides was about 1.5-2.5μm. The wafer was cleaned with a standard RCA process and immersed in a dilute hydrofluoric acid solution, and then transferred to a deposition device (AKT-25KAXi PECVD system). Radio frequency plasma enhanced chemical vapor deposition was used to prepare a surface passivation stack, depositing about 6nm of hydrogenated intrinsic a-Si:H and 14nm of hydrogenated n-doped nc-Si:H on the front side. Subsequently, 8nm of hydrogenated intrinsic-Si:H and 10nm of hydrogenated p-doped a-Si:H layers were deposited on the back side. The opening area is 12×12mm 2 Using an alignment mask, ITO layers with a thickness of 10 nm and 115 nm were prepared on the front and back sides by DC sputtering, respectively. To recover the sputtering damage, a 10-min annealing step at 200 °C in ambient air was also performed. The wafer was then laser-etched into 25 × 25 mm 2 size.
[0139] 2. Silicon heterojunction bottom cell cleaning: The substrate was cleaned by ultrasonic cleaning in ethanol for 20 minutes, and then the ITO substrate was dried in a 70°C oven for 1 hour and then treated with ultraviolet ozone (UVO) for 10 minutes.
[0140] 3. Prepare the hole transport layer on the silicon heterojunction bottom cell. The ethanol solution (2 mg mL -1) was spin-coated on the ITO conductive layer at a speed of 3000 rpm, and then annealed at 100° C. for 30 minutes to prepare a hole transport layer.
[0141] 4. Prepare the perovskite active layer. Configure the wide-bandgap perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 precursor solution (1.68eV), FAI, MABr, CsI, PbBr2, MAI, PbI2 were added to 1mL DMF / DMSO (v / v, 4:1) solution. Then 100μL of the perovskite precursor solution was directly spin-coated onto the hole transport layer, first at 1500r / min for 10s, then at 3500r / min for 35s. The resulting film was then transferred to a hot stage and annealed at 100°C for 30 minutes to obtain a perovskite film.
[0142] 5. Deposit an electron transport layer on the perovskite layer. A 25 nm thick C60 layer was prepared on the prepared perovskite film by thermal evaporation.
[0143] 6. Deposit a buffer layer on the electron transport layer. Deposit 13nm tin oxide as a sputtered buffer layer by atomic layer deposition system. The processing sequence of ALD SnO2 deposition is: 0.15s TDMASn pulse, 12s purge (50sccm Ar), 0.33s deionized water pulse, 12s purge (50sccm Ar), for a total of 120 cycles.
[0144] 7. Magnetron sputtering of transparent electrode IZO on the buffer layer. At room temperature, 100 nm IZO (sheet resistance of 30-40 Ω / sq, radio frequency (RF) power of 45 W) was sputtered on the prepared buffer layer.
[0145] 8. Deposit an anti-reflection layer on the transparent electrode. 150nm of MgF2 is deposited on the prepared transparent electrode.
[0146] The performance and stability of the obtained single-cell perovskite solar cell and perovskite / crystalline silicon tandem solar cell were tested, and the results are shown in Figure 6-Figure 8 . Figure 6 The current density and voltage (JV) curves of the single-cell perovskite solar cells prepared in Comparative Example 1 and Example 6; Figure 7 The current density and voltage (JV) curves of the perovskite / crystalline silicon stacked perovskite solar cells prepared in Comparative Example 2 and Example 7; Figure 8 The results of the light stability test of the single-cell perovskite solar cell prepared in Comparative Example 1 and Example 6 under MPP (25°C, nitrogen) are shown in FIG. Figure 6The results obtained are shown in Table 1, which shows the detailed parameters of open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of Comparative Example 1, Comparative Example 2, Example 6 and Example 7.
[0147] Table 1 Detailed parameters of open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of Comparative Example 1, Comparative Example 2, Example 6 and Example 7:
[0148]
[0150] As can be seen from Table 1, compared with Comparative Example 1, the efficiency of a single-section wide bandgap (1.68 eV) perovskite solar cell device prepared with a strongly adsorbed superwetting self-assembled small molecule as a hole transport layer is increased from 21.60% to 22.83%. By further preparing a stacked solar cell, Example 7 has a photoelectric conversion efficiency of nearly 30%, compared with only 27.91% in Comparative Example 2. This proves that strongly adsorbed superwetting self-assembled small molecules as a hole transport layer can prepare high-quality perovskite films with minimal energy mismatch, thereby improving the performance of solar cells. This is mainly because the reverse-substituted carbazole ring contributes to a friendly superwetting bottom layer, while weakening the amphiphilic properties of the carbazole-based SAM, which helps to break the distance between molecules in the solution state and achieve a more dense self-assembled film.
[0151] Figure 8 The light stability test results of the perovskite solar cell devices of Comparative Example 1 and Example 6 under MPP (25°C, nitrogen) are shown in FIG. Figure 8 It can be seen that under the condition that the device is not encapsulated, the perovskite solar cell device using the strongly adsorbed superwetting self-assembly molecule I-1 can still maintain more than 95% of the original photoelectric conversion efficiency after 1000 hours of illumination (25°C, nitrogen), while the efficiency of the perovskite solar cell device of comparative example 1 drops by about 20% after 1000 hours of illumination.
[0152] See also Fig. 9 A novel bidentate-anchored superwettable aromatic self-assembled monolayer is used as a hole-selective layer (HSL) in inverted wide-bandgap perovskite solar cells (PSCs). The reverse substitution of carbazole plays an important role in promoting the formation of a robust HSL and improving the hole extraction and transport efficiency. The optimized wide-bandgap PSC achieves a photoelectric conversion efficiency (PCE) of 22.83%, while the fabricated p-type / n-type structured perovskite solar cell (P / S-TSC) achieves an efficiency of up to 32.19%, while exhibiting excellent wet-thermal stability.
[0153] In summary, the invention provides a method for preparing a strongly adsorbed superwetting self-assembled small molecule, and uses it as a hole transport layer in a pin-type single-section perovskite solar cell and a perovskite / crystalline silicon stacked solar cell, which can provide a perovskite-friendly superwetting bottom layer, achieve a high-quality perovskite film with minimized energy loss, and greatly improve the performance of single-section and stacked perovskite solar cells. At the same time, the dual anchoring linking groups give I-1 enhanced adsorption capacity on planar and textured ITO surfaces, improving the photostability of perovskite solar cells.
[0154] It should be emphasized that the term “include / comprises” when used herein refers to the presence of features, elements, steps or components, but does not exclude the presence or addition of one or more other features, elements, steps or components.
[0155] In addition, the method of the present invention is not limited to being executed in the time sequence described in the specification, and may also be executed in other time sequences, in parallel or independently. Therefore, the execution order of the method described in this specification does not limit the technical scope of the present invention.
[0156] Although the present invention has been disclosed above by describing specific embodiments of the present invention, it should be understood that all the above embodiments and examples are exemplary rather than restrictive. Those skilled in the art may design various modifications, improvements or equivalents of the present invention within the spirit and scope of the appended claims. These modifications, improvements or equivalents should also be considered to be included in the protection scope of the present invention.
Claims
1. A strongly adsorbed superwetting self-assembling small molecule, characterized in that: It has the structure shown in Formula I: In Formula I, is an aromatic conjugated group, R 1 is hydrogen, methyl, methoxy or halogen, R 2 It is a phosphonic acid group, a carboxylic acid group or a cyanophosphate group.
2. The strongly adsorbed superwetting self-assembling small molecule according to claim 1, characterized in that: The aromatic conjugated group Any one of the following groups:
3. A method for preparing a strongly adsorbed superwetting self-assembling small molecule, characterized in that: The following steps are involved: Step (1): using the compound represented by the 3,6-dibromocarbazole derivative formula A as a starting material and conducting a borate esterification reaction with biboric acid pinacol ester B to obtain a compound represented by the formula C, and the reaction formula is as follows: Step (2): The compound represented by formula C undergoes a Suzuki coupling reaction with the compound represented by formula D to generate the compound represented by formula E. The reaction formula is as follows: Step (3): The compound represented by Formula E undergoes a nucleophilic substitution reaction with Formula F to generate a compound represented by Formula G. The reaction formula is as follows: Step (4): The compound represented by formula G is hydrolyzed with trimethylsilyl bromide to obtain the compound represented by formula I. The reaction formula is as follows: Among them, R 1 is hydrogen, methyl, methoxy or halogen, R 2 is a phosphonic acid group, a carboxylic acid group or a cyanophosphate group, R 3 is a phosphonate group, a carboxylate group or a cyanophosphate group, Any one of the following groups:
4. The preparation method according to claim 3, characterized in that: In the step (1), the molar mass ratio of the compound of formula A to the compound of formula B is 1:(2.0-4.0).
5. The preparation method according to claim 3, characterized in that: In the step (2), the molar mass ratio of the compound of formula C to the compound of formula D is 1:(4.0-6.0).
6. The preparation method according to claim 3, characterized in that: In the step (3), the molar mass ratio of the compound of formula E to the compound of formula F is 1:(4.0-8.0).
7. The preparation method according to claim 3, characterized in that: In the step (4), the molar mass ratio of the compound of formula G to trimethylsilyl bromide is 1:(40.0-60.0).
8. A hole transport layer, characterized in that: The strongly adsorbed superwetting self-assembled small molecules as claimed in claim 1 or 2 are used as hole transport materials.
9. A perovskite solar cell, characterized in that: The hole transport material as claimed in claim 8 is used as a hole transport layer.
10. The perovskite solar cell according to claim 9, characterized in that: The perovskite solar cell comprises an anode layer, a hole transport layer, a perovskite active layer, an electron transport layer and a cathode layer stacked in sequence; wherein the concentration of the hole transport material is 0.25 mg / mL-2.5 mg / mL.
Citation Information
Patent Citations
Self-assembled monomolecular layer material as well as preparation method and application thereof
CN118239979A
Cited By
Perovskite solar cell, preparation method thereof and photovoltaic module
CN121001503A
Indenocarbazole-based bisphosphonic acid self-assembled monolayer material, synthesis method and application thereof
CN122726210A